Developing Representative Dual Loading Protocols for the Columns of Steel Special Moment Frames based on the Seismic Demands on These Members. Issue 8 (17th November 2017) - Farahi, Mojtaba; Erfani, Saeed
Abstract : The column members of steel moment frames undergo high axial forces as well as inelastic rotations during a severe seismic event. The boundaries of these simultaneous structural demands on the columns of special moment frames have been investigated in this research. Based on the results of this investigation, dual cyclic loading protocols have been developed that represent both axial force and lateral deformation demands. Contrary to other loading scenarios that have been implemented in previous studies on steel columns, the loading protocols developed in this study include simultaneous axial and lateral loading cycles with varying amplitudes. The level of axial forces and story drifts tolerated by the columns of some typical Special Moment Frames (SMFs) has been investigated through performing nonlinear dynamic analyses. These frames have been selected with several configurations and different number of stories. The results of the nonlinear dynamic analyses have been processed to assess cumulative and instantaneous seismic demands on the columns of the chosen typical frames. Subsequently, dual cyclic loading protocols have been developed such that exerting these loading protocols on individual steel columns can result in structural effects close to the general seismic demands assessed in this study. Two separate dual loading protocols have been introduced for Design Earthquake (DE) and Maximum Considered Earthquake (MCE) seismic intensity levels.